2012
DOI: 10.1258/acb.2011.011224
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a macro-alkaline phosphatase complex in a patient with inflammatory bowel disease

Abstract: We report the rare finding of a macro-alkaline phosphatase (macroALP) complex in a patient with a previously unexplained raised alkaline phosphatase activity. The clinical symptoms were persistent, daily diarrhoea for two months with blood in the stool. The patient was subsequently diagnosed with inflammatory bowel disease, specifically ulcerative colitis, following a rectal biopsy and colonoscopy. Two cases of macroALP associated with ulcerative colitis have been reported before, suggesting there could be an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Maekawa et al [8] suggested that ALP was attached through the F (ab′) 2 fragment of IgA and that the molecular weight of the complexes suggested that 2 molecules of ALP was associated with one molecule of divalent IgA. Characterisation of the macro-ALP was performed by gel filtration [7], immunoelectrophoresis [7], PEG precipitation [11], and proteolytic digestion [9]. Protein A/G agarose affinity chromatography was used to demonstrate the presence of macro-ALP [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maekawa et al [8] suggested that ALP was attached through the F (ab′) 2 fragment of IgA and that the molecular weight of the complexes suggested that 2 molecules of ALP was associated with one molecule of divalent IgA. Characterisation of the macro-ALP was performed by gel filtration [7], immunoelectrophoresis [7], PEG precipitation [11], and proteolytic digestion [9]. Protein A/G agarose affinity chromatography was used to demonstrate the presence of macro-ALP [12].…”
Section: Discussionmentioning
confidence: 99%
“…Macro-ALP has been reported in patients with ulcerative colitis [11], carcinoma of prostate [10], bronchopneumonia and recurrent infections [9], and liver cirrhosis and cholestasis [6]. Atypical ALP with posttranslational modification has been described in a patient with Hodgkin's disease [14].…”
Section: Discussionmentioning
confidence: 99%
“…Macro-ALP (e.g. immunoglobulin-ALP complexes) have also been described in several case reports, although such cases specifically refer to human Abs bound to human ALP [[18], [19], [20]].…”
Section: Discussionmentioning
confidence: 99%
“…There is however still a smattering of interesting papers describing novel isoforms, the most recent appearing in 2012. 20 It is good to see that this enzyme still interests clinical biochemists today, but the heady days of Barron's 'new magic', when many of the old academic departments were led by enzymologists who could claim an almost apostolic line of descent from Earl King, are well and truly gone.…”
mentioning
confidence: 99%